2018
DOI: 10.3390/s18124443
|View full text |Cite
|
Sign up to set email alerts
|

Posture-Specific Breathing Detection

Abstract: Human respiratory activity parameters are important indicators of vital signs. Most respiratory activity detection methods are naïve abd simple and use invasive detection technology. Non-invasive breathing detection methods are the solution to these limitations. In this research, we propose a non-invasive breathing activity detection method based on C-band sensing. Traditional non-invasive detection methods require special hardware facilities that cannot be used in ordinary environments. Based on this, a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The ANOVA results showed that IJP sensor had high accuracy, good repeatability, and stability at different body postures. With no observable deviation from the reference sensor at all body postures, the accuracy of the IJP sensor was better than many sensors reported in the literature where the RR measured by stretchable sensor deviated from the reference value from 1.7% to more than 6% in different postures [4,12,[26][27][28][29][30].…”
Section: Ijp Sensor Accuracy: Comparison With Other Sensorsmentioning
confidence: 68%
See 4 more Smart Citations
“…The ANOVA results showed that IJP sensor had high accuracy, good repeatability, and stability at different body postures. With no observable deviation from the reference sensor at all body postures, the accuracy of the IJP sensor was better than many sensors reported in the literature where the RR measured by stretchable sensor deviated from the reference value from 1.7% to more than 6% in different postures [4,12,[26][27][28][29][30].…”
Section: Ijp Sensor Accuracy: Comparison With Other Sensorsmentioning
confidence: 68%
“…Some researchers extract RR from other physiological signals such as photoplethysmogram and electrocardiogram [11]. Other studies derived respiration signals using non-contact techniques such as C-band sensing [12] and dual smartphone cameras [4]. Some researchers tried distant (less than 10 m) RR detecting based on Wi-Fi, radar, or thermal imaging [11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations